The Students' Perspective Towards YouTube as the Replacement of Lecturer in Nahwu Learning - Marsiah, Marsiah; Mubarak, Mahfuz Rizqi; Audina, Noor Amalina (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2021)
The existence of YouTube social media as a medium to support the Arabic learning process has been widely discussed by researchers. However, the existence of this media has the potential for misunderstanding of educators in implementing YouTube as a substitute for the role of educators in the learning process. This article aims to explore students' perspectives regarding the phenomenon of misunderstanding in Nahwu science learning and recommendations so that the lecture process can run effectively. Narrative approach was used in this research. The research data were obtained from interviews with 32 students from various districts in Central Kalimantan Province. From the results of the study, it was found that students gave positive and negative perceptions about Nahwu science learning using the YouTube media. However, negative perceptions dominate more with various expressions of disappointment from students. The students definitely felt aggrieved by the implementation of the Nahwu lecture which was limited to using the YouTube media without being accompanied by further explanations from the lecturers who taught the Nahwu course. Students recommend lecturers to be more involved in the Nahwu lecture process rather than simply sharing video material that is already available on YouTube media.